Construction of a novel methylation‐related prognostic model for colorectal cancer based on microsatellite status. Issue 12 (16th August 2021) - Cao, Lichao; Chen, Erfei; Zhang, Hezi; Ba, Ying; Yan, Bianbian; Li, Tong; Yang, Jin
Abstract: The present study aimed to construct a novel methylation‐related prognostic model based on microsatellite status that may enhance the prognosis of colorectal cancer (CRC) from methylation and microsatellite status perspective. DNA methylation and mRNA expression data with clinical information were downloaded from The Cancer Genome Atlas (TCGA) data set. The samples were divided into microsatellite stability and microsatellite instability group, and CIBERSORT was used to assess the immune cell infiltration characteristics. After identifying the differentially methylated genes and differentially expression genes using R packages, the methylation‐driven genes were further identified. Prognostic genes that were used to establish the methylation‐related risk score model were generated by the univariate and multivariate Cox regression model. Finally, we established and evaluated the methylation‐related prognostic model for CRC patients. A total of 69 MDGs were obtained and three of these genes ( MIOX, TH, DKFZP434K028 ) were selected to construct the prognostic model. Patients in the low‐risk score group had a conspicuously better overall survival than those in the high‐risk score group ( p  < .0001). The area under the receiver operating characteristic curve for this model was 0.689 at 3 years, 0.674 at 4 years, and 0.658 at 5 years. The Wilcoxon test showed that higher risk score was associated with higher T stage ( p  = .01), N stages ( p  = .0028), metastasis ( p  = .013), and advanced pathological stage ( p  = .0013). However, the more instability of microsatellite status, the lower risk score of CRC patients ( p  = .0048). Our constructed methylation‐related prognostic model based on microsatellite status presents potential significance in assessing recurrence risk stratification, tumor staging, and immunotherapy for CRC patients.